ANALISIS PEMASARAN KOPI ARABIKA DI DESA SIHITE I KECAMATAN DOLOK SANGGUL KABUPATEN HUMBANG HASUNDUTAN - Lumban Batu, Tio; Simanullang, Endang Sari (Fakultas Pertanian UST, 2024)
This research aims to analyze the marketing of Arabica coffee in Sihite I Village, Dolok Sanggul District, Humbang Hasundutan Regency. This research has a sample size of 40 coffee farmers, 2 collecting traders, 2 diluent traders, 1 wholesaler in Sihite Village, Dolok Sanggul District, Humbang Hasundutan Regency. Considering the importance of the Arabica coffee commodity for farmers, a clear picture of the Arabica coffee marketing channel from farmer producers to final consumers is needed so that profits can be distributed evenly. This research was carried out starting from a survey, collecting data in the field and making a report. The research results show that there are two marketing channels, namely marketing channel 1 consisting of farmers and wholesalers and consumer channel 2 consisting of farmers, collecting traders, retailers, wholesalers and consumers. Marketing costs in Sihite I Village, Dolok Sanggul District, Humbang Hasundutan Regency with marketing costs of IDR 180.52/Kg and the highest marketing margin in level 2 marketing channels of IDR 25,000/Kg. Keywords: Arabica Coffee, Marketing Channels, Costs, Margin